Cytotoxic cell involvement in human cutaneous leishmaniasis: assessments in active disease, under therapy and after clinical cure. (April 2016) - Cunha, C. F.; Ferraz, R.; Pimentel, M. I. F.; Lyra, M. R.; Schubach, A. O.; Da‐Cruz, A. M.; Bertho, A. L.
Summary: Cutaneous leishmaniasis (CL) is an important public health issue worldwide. The control of Leishmania infection depends on cellular immune mechanisms, and the inflammatory response may contribute to pathogenesis. A beneficial role of CD8 + T lymphocytes has been proposed; nevertheless, other studies suggest a cytotoxic role of CD8 + T lymphocytes involved in tissue damage, showing controversial role of these cells. The goal of the current study was to understand the immunopathology of CL and determine the profile of cytotoxic cells – such as CD4 + T, natural killer and natural killer T cells – that might be involved in triggering immunological mechanisms, and may lead to cure or disease progression. The frequencies of cytotoxic cell populations in peripheral blood, obtained from patients with active disease, during treatment and after clinical healing, were assessed by flow cytometry. Cytotoxicity could not be related to a deleterious role in Leishmania braziliensis infection, as patients with active CL showed similar percentages of degranulation to healthy individuals (HI). Cured patients exhibited a lower percentage of degranulating cells, which may be due to a downregulation of the immune response. The understanding of the immunopathological mechanisms involved in CL and the commitment of cytotoxic cells enables improvements in therapeutic strategies.